EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE, NUMBERED HEADS TOGETHER DAN PROBLEM BASED LEARNING DENGAN PENDEKATAN SAINTIFIK PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DITINJAU DARI KONSEP DIRI - Darmawan, Agus; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of this research was to investigate the effect of learning models on mathematics achievement viewed from the student self concept. The learning model compared were Think Pair Share, Numbered Heads Together dan Problem Based Learning with saintific approach (TPS-S, NHT-S and PBL-S). This research was a quasi experimental with the factorial design of 3×3. The population of this research was all of students in grade VII of State Islam Junior High Schools of Magetan regency in academic year 2014/2015. The samples of the research consisted of 243 students and were gathered through stratified cluster random sampling. The instruments consisted of the test of learning achievement and self concept questionnaire. Hypotheses testing was performed using two-way analysis of variance with unbalanced cells. Based on the results of hypotheses testing, it was concluded as follows. 1) Students with the cooperative learning model of the TPS-S, NHT-S and PBL-S learning model had the same mathematics achievement. 2) Students with high self concept had better mathematics achievement than students with medium and low self concept, students with medium self concept and low self concept have the same mathematics achievement. 3a) On the TPS-S learning model, students with high self concept had better mathematics achievement than students with low self concept, students with high self concept and medium self concept have the same mathematics achievement, students with medium self concept and low self concept have the same mathematics achievement. 3b) On the NHT-S and the PBL-S learning models, students mathematics achievement on each self concept categories had the same mathematics achievement. 4) On the each students self concept categories, students achievement on each learning model types had the same mathematics achievement.Keywords: Think Pair Share (TPS), Numbered Heads Together (NHT), Problem Based Learning (PBL), Scientific Approach and Self Concept.